Nine heteroleptic copper(I)/silver(I) complexes prepared from phosphine and diimine ligands: syntheses, structures and terahertz spectra. (1st January 2020) - Sun, Ling-Zhi; Kuang, Xiao-Nan; Lin, Sen; Zhao, Li; Yu, Xiao; Li, Zhong-Feng; Min-Liu,; Xin, Xiu-Lan; Yang, Yu-Ping; Jin, Qiong-Hua
Graphical abstract: Nine different copper(I)/silver (I) complexes were synthesized by changing anions and ligands. All these nine complexes exhibit intriguing 1D-3D structures which is due to intermolecular interactions. These complexes display interesting luminescence in the solid state at room temperature. In addition, THz spectroscopy was also studied in this research. Abstract: Direct reactions under ambient conditions among copper/silver salts, diimine ligands and diphosphine ligands were carried out at different rations, generating nine novel Cu(I)/Ag(I) complexes, [Cu(Dpq)(dppp)](ClO4 ) (1 ), [Cu(Dppz)(dppp)](ClO4 ) (2 ), [Cu(Dpq)(POP)](ClO4 ) (3 ), [Cu(Dppz)(POP)](ClO4 ) (4 ), [Cu(Dpq)(xantphos)](ClO4 )·0.843CH2 Cl2 (5 ), [Cu(Dppz)(xantphos)](ClO4 )·2CH2 Cl2 (6 ), [Ag(Dpq)(xantphos)](ClO4 ) (7 ), [Ag(Dpq)(xantphos)](CF3 SO3 ) (8 ), [Ag(Dpq)(POP)](CF3 SO3 ) (9 ). {Dpq = pyrazino[2, 3-f][1, 10]phenanthroline, Dppz = dipyrido[3, 2-a:2′, 3′-c]phenazine, POP = 1, 1′-[(Oxydi-2, 1-phenylene)]bis[1, 1-diphenylphosphine], xantphos = 9, 9-dimethyl-4, 5-bis(diphenylphosphanyl)xanthene, dppp = 1, 3-bis(diphenylphosphine)propane). Their crystal structures have been determined by single crystal X-ray diffraction and they were characterized by IR, UV, elemental analysis, fluorescence spectra, 1 H NMR and 31 P NMR spectroscopy. All above nine Cu(I)/Ag(I) complexes have intriguing crystal stacking structures. Complexes 3, 9 are of 1D infinite chain structures formed by C–H⋯π interactions between each adjacent molecule while complexes 1, 2, 5, 6, 8 are of 2D network structures because of hydrogen bonds, C–H⋯π interactions and π⋯π interactions. However, complex 4 is complicated three-dimensional structure formed by C–H⋯π interactions. Some of the complexes exhibit obvious luminescence in the solid state, and interesting photoluminescence phenomenon are explained in detail. Among these six Cu(I) complexes, complex 5 shows the highest quantum yield up to 17.2%, which is due to the large steric hindrance of xantphos ligand. For these three Ag(I) complexes, complex 8 displays the highest quantum yield of 19.5%. In addition, the terahertz time-domain spectrum (THz-TDS) of these complexes has been investigated in detail leading to the preliminary discovery of correlation between terahertz spectra and crystal packing of complexes.